2017
DOI: 10.1590/s1806-92902017000800008
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical parameters of Brazilian sport horses under training in tropical climate

Abstract: -This study aimed to provide baseline data for the serum biochemical parameters of Brazilian sport horses undergoing physical training for eventing to be used as a practical guide. A total of 139 blood samples were collected by vacuum venipuncture of the jugular vein from healthy horses in training. Tubes without anticoagulant were used for biochemical analysis. Means and standard deviations were determined for aspartate aminotransferase (AST) (306.27±84.66 U/L), creatine kinase (CK) (181.06±80.38 U/L), urea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
3
7
0
2
Order By: Relevance
“…The groups treated with haylage presented a discrete decrease that persisted for three weeks (T1, T2 and T3). Mean values observed in both G1 and G2 ranged respectively from 200.43U/L to 259.97U/L and 138.39U/L to 230.23U/L, similarly to those reported by Souza et al (2016) of 140U/L and Padilha et al (2017) with means of 246.34U/L. According to Kaneko & Harvey (1997) all values remained within the normal range (226-366 U/L).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The groups treated with haylage presented a discrete decrease that persisted for three weeks (T1, T2 and T3). Mean values observed in both G1 and G2 ranged respectively from 200.43U/L to 259.97U/L and 138.39U/L to 230.23U/L, similarly to those reported by Souza et al (2016) of 140U/L and Padilha et al (2017) with means of 246.34U/L. According to Kaneko & Harvey (1997) all values remained within the normal range (226-366 U/L).…”
Section: Resultssupporting
confidence: 79%
“…Haylage group showed similar values, 12.9±4.71U/L (T0) e 19.2±9.10U/L (T4), but without statistic increase. Although discrete alterations occurred, all values remained within the normal limit for equine (9 to 26U/L) according to Padilha et al (2017), demonstrating that no cholangitis or cholestasis occurred.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The aim of this study was to investigate whether training of Arabian horses could change some serum biochemical variables, trace elements, and electrolytes before and after exercise or not. Researchers suggested that exercise in horses could change some biochemical parameters of serum that were related to different factors such as individual differences, breed, and the level of exercise [12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Urea and creatinine are commonly used for the evaluation of kidney function. The concentrations of these two factors may be affected by dehydration and exercise [12].…”
Section: Introductionmentioning
confidence: 99%